AKHLAK PELAJAR DITINJAU DARI KITAB ADAB AL-ALIM WA AL-MUTA’ALLIM - Nailul Fitria Afifah; Sania Ro’ifah (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2019)
Understanding of the concept of learning in Islamic education and also the concept of student ethics according to Kyai Haji Hasyim Asy'ari in the book adab Ta'lim Muta'alim. The purpose of this study is so that student tools in learning can facilitate the achievement of appropriate character education. The results of the study state that the principle that students must have is a pure heart straightens out the intention to seek knowledge qanaah can divide the time to reduce eating and drinking reduce sleep and avoid association with the opposite sex. The method in this study is that student library research in the view of Kyai Haji Muhammad Hasyim Asy'ari is a person who must have full continuity and concentration in participating in learning activities that have high mortality and motivation so that students are not trapped in pragmatism while seeking knowledge.Keywords: Morals, Ta'lim Muta'alim